Effect weight ratio of bamboo schizostachyum grande fiber treated by silane coupling agent - Roseli, Adyla Illyana; Mat Hassan, Nik Normunira; Yahya, Nur Faezah; Atil, Aida Atiqah; Darlis, Nofrizalidris; Roslan, Mohd Nazrul; Tuan Ismail, Tuan Noor Hasanah; Mohamed Yusop, Fatimah; Johan, Nur Ain Arina (2024)
. Bamboo fiber has gained popularity in Malaysia and it is increasingly used in the production of green composites such as construction applications, roofs, flooring, and sports equipment. In this study, the Bamboo Schizostachyum Grande fiber was treated with a silane coupling agent to examine the physical characterization using TGA, SEM, and FTIR. The SEM was analyzed before (untreated) and after treatment (treated) with different weights of bamboo fiber. The results of SEM demonstrate that the bamboo fiber was treated, and the surface morphology and chemical elements reacting to silane coupling agents were improved, which shows the layer and bamboo fiber were expanded up to 7 mm than untreated. TGA results shows of the thermal degradation of untreated bamboo fiber occur at 341.08°C, which is significantly lower than the thermal degradation of 0.3 g of treated bamboo fiber at 354.84°C. It reveals that the surface compatibility and bonding strength of bamboo fiber treated with a silane coupling agent are more effective than untreated bamboo. The highest weight of bamboo fiber shows good thermal stability was 0.7 g. FTIR spectrum shows the peak from 2890 cm-1 to 2898 cm-1 indicating that treated fiber was absorbed by silane coupling agents, but the different weights of bamboo fiber exhibited significantly no effect, and the results show treated 0.3, 0.4. 0.6, 0.7 g peaks continuously from 2890 to 2898 cm-1 while the untreated bamboo fiber cellulose structure did not show any additional groups at this range. Hence, this silane coupling agent treatment performed better than untreated and it has the potential to be used in insulating and hydrophobic applications